Lithium ion battery electrolyte suitable for high-voltage working condition and ternary lithium ion battery thereof
By adding fluoroborate electrolyte additives to the lithium-ion battery electrolyte solution, the problem of poor circulation performance of lithium-ion batteries under high-voltage working conditions is solved, and higher high-voltage resistance and circulation capacity retention rate are achieved, improving the safety of the battery.
Patent Information
- Application Number
- CN202311205831.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
Existing lithium-ion batteries have poor cycling performance under high-voltage working conditions, making it difficult to effectively improve the high-voltage resistance of ternary lithium-ion batteries.
The addition of fluoroborate ester electrolyte additives to the lithium-ion battery electrolyte solution is used as a supplement to conventional film-forming electrolyte additives to form a stable interface film to inhibit the side reaction between the electrolyte and the electrode interface under high pressure conditions.
By adding fluoroborate compounds, the high-voltage resistance of lithium-ion batteries is significantly improved, the expansion rate of the battery is reduced, the circulation capacity retention rate is improved, and the safety performance of the battery is enhanced at high temperatures and high voltages.
Smart Images

Figure CN119650847A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to a lithium ion battery electrolyte suitable for high voltage working conditions and a ternary lithium ion battery thereof. Background Art
[0002] As the requirements for lithium-ion battery capacity in electrical equipment continue to increase, people have higher and higher expectations for the improvement of lithium-ion battery energy density. Ternary lithium-ion batteries have attracted the attention of researchers due to their high energy density. However, in order to design high-energy-density ternary lithium-ion batteries, in addition to continuously optimizing their space utilization, improving the compaction density and gram capacity of the positive and negative electrode materials of the battery, and using highly conductive carbon nanotubes and polymer adhesives to increase the content of active materials in the positive and negative electrodes, increasing the working voltage of lithium-ion batteries is also one of the important ways to increase the battery energy density.
[0003] There are two main solutions at present: one is to modify the positive electrode material, such as ion doping, material surface coating, etc.; the other is to develop new electrolyte additives. The new electrolyte film-forming additive can form a protective film in the battery system, thereby cutting off the direct contact between the electrode material and the electrolyte. It is one of the most effective methods so far. It avoids the poor cycle performance of lithium-ion batteries caused by the oxidation and decomposition of the electrolyte by the positive electrode material under high pressure conditions. Therefore, it is particularly important to develop an electrolyte that matches the ternary material lithium battery.
[0004] CN109830752A uses cyclic fluorocarbonate and cyclic carbonate as solvents to improve the high-voltage resistance of the battery. However, changing the solvent system is generally not applicable in commercial applications. Compared with the prior art, this patent proposes to add fluoroborate electrolyte additives, which improves the high-voltage resistance of ternary ion batteries without changing the commonly used carbonate solvent system, and has more general applicability and operability. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium ion battery electrolyte suitable for high voltage working conditions and its application, which has solved the problems raised in the above background technology.
[0006] In order to achieve the above-mentioned object, a first aspect of the present invention provides a lithium ion battery electrolyte suitable for high voltage working conditions, the lithium ion battery electrolyte comprising: a lithium salt, an organic solvent and an additive;
[0007] The additive comprises a conventional film-forming electrolyte additive and an additive A, wherein the additive A is selected from at least one of the fluoroboric acid ester compounds represented by formula (I).
[0008]
[0009] In formula (I), R is C1~C 10 A fluorinated alkyl group, preferably a C1-C3 fluorinated alkyl group, wherein R1, R2, R3, and R4 are each independently selected from H, F, or C1-C 10 Containing a fluorinated alkyl group, and R1, R2, R3, and R4 are not H at the same time;
[0010] Based on the total mass of the electrolyte, the content of the additive A is 0.01-3.0 wt %, preferably 0.1-0.8 wt %.
[0011] The second aspect of the present invention provides a ternary lithium-ion battery, comprising: a positive electrode sheet, a separator, a negative electrode sheet and the lithium-ion battery electrolyte.
[0012] Compared with the prior art, the present invention is beneficial in that:
[0013] (1) In the fluoroborate compounds of the present invention, R contains a fluoroalkyl group. The presence of this structure can stabilize the SEI film and inhibit the decomposition of the solvent under high pressure.
[0014] (2) The fluoroborate compounds of the present invention contain carbon-carbon double bonds, which can be reduced and oxidized on the surfaces of the positive and negative electrodes to form a stable interface film (SEI / CEI), thereby inhibiting the side reactions at the interface between the electrolyte and the electrode under high-voltage conditions.
[0015] (3) The fluoroborate compounds of the present invention contain a borate group, which is an anion receptor. The empty p orbital of B is in an electron-deficient state, making it acidic and able to complex with PF6 - or F - , improve Li + The migration number can be increased and the content of LiF on the electrode surface can be reduced, thereby effectively alleviating the problem of excessive battery impedance caused by the carbon-carbon double bonds in fluoroborate compounds.
[0016] (4) The present invention provides a high-temperature electrolyte suitable for a high-nickel system, wherein the additive A in the electrolyte can generate a stable interface film (SEI / CEI), thereby inhibiting side reactions at the electrolyte and electrode interface under high temperature conditions.
[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.
[0019] Figure 1 A comparison chart of the battery cycle capacity retention rates of Example 3 and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0020] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0021] In order to achieve the above-mentioned object, a first aspect of the present invention provides a lithium ion battery electrolyte suitable for high voltage working conditions, the lithium ion battery electrolyte comprising: a lithium salt, an organic solvent and an additive;
[0022] The additive comprises a conventional film-forming electrolyte additive and an additive A, wherein the additive A is selected from at least one of the fluoroboric acid ester compounds represented by formula (I).
[0023]
[0024] In formula (I), R is C1~C 10 A fluorinated alkyl group, preferably a C1-C3 fluorinated alkyl group, wherein R1, R2, R3, and R4 are each independently selected from H, F, or C1-C 10 Containing a fluorinated alkyl group, and R1, R2, R3, and R4 are not H at the same time;
[0025] Based on the total mass of the electrolyte, the content of the additive A is 0.01-5.0 wt %, preferably 0.1-3.0 wt %.
[0026] According to the present invention, preferably, the preparation method of the additive A comprises the following steps:
[0027] The preparation method of the additive A comprises the following steps:
[0028] (1) dissolving the fluorinated halogenated olefin represented by formula (II) and pinacol borane in a first organic solvent, heating to 50-60° C., and contacting with a catalyst to react to generate an intermediate product, fluoroallyl boronic acid pinacol ester; the molar ratio of the fluorinated halogenated olefin to the pinacol borane is 1:1;
[0029] (2) dissolving the intermediate product fluoroallyl boronic acid pinacol ester produced in step (1) and the fluorinated ketone substance represented by formula (III) in a second organic solvent, heating to 50-60° C., and stirring for reaction to produce the additive A; the molar ratio of the intermediate product fluoroallyl boronic acid pinacol ester to the fluorinated ketone substance is 1:1;
[0030] Formula (II) and formula (III) are as follows:
[0031]
[0032] Wherein, in formula (II), R is C1~C 10A fluorinated alkyl group, preferably a C1-C3 fluorinated alkyl group; in formula (3), R' and R" are each independently selected from C1-C 10 At least one of fluorinated alkyl groups;
[0033] The first organic solvent is dimethyl sulfoxide solvent;
[0034] The second organic solvent is tetrahydrofuran;
[0035] The catalyst is Pd2(dba)3.
[0036] According to the present invention, preferably, the additive A can be any one of the following fluoroborates:
[0037]
[0038] (a) 4,5-difluoro-2-(4,4,4-trifluorobut-2-en-1-yl)-1,3,2-dioxaborolane
[0039] According to the present invention, in a specific embodiment, the synthesis route of 4,5-difluoro-2-(4,4,4-trifluorobut-2-ene-1-yl)-1,3,2-dioxaborane is as follows:
[0040]
[0041]
[0042] (b) Fluoro-2-(3-fluoroallyl)-1,3,2-dioxaborolane
[0043]
[0044] (c) 4,5-difluoro-2-(3-fluoroallyl)-1,3,2-dioxaborolane
[0045]
[0046] (d) 4-Fluoro-2-(3-fluoroallyl)-5-fluoromethyl-1,3,2-dioxaborolane
[0047]
[0048] (e) 2-(3-Fluoroallyl)-4,5-bisfluoromethyl-1,3,2-dioxaborolane.
[0049] According to the present invention, preferably, the conventional film-forming electrolyte additive is selected from at least one of difluorophosphate (LiPO2F2), vinyl sulfate (DTD), vinylene carbonate (VC) and propylene sulfite (PS).
[0050] Further preferably, based on the total mass of the electrolyte, the content of the conventional film-forming electrolyte additive is 3.0-5.0 wt %.
[0051] According to the present invention, preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium perchlorate and lithium hexafluoroarsenate, preferably selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.
[0052] Further preferably, based on the total mass of the electrolyte, the content of the lithium salt is 0.5-3wt%.
[0053] According to the present invention, preferably, the organic solvent is a carbonate compound; preferably, the carbonate compound includes cyclic carbonates and chain carbonates; wherein the cyclic carbonate is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC) and fluoroethylene carbonate (FEC); and the chain carbonate is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).
[0054] According to the present invention, preferably, the organic solvent is a mixture of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and diethyl carbonate (DEC).
[0055] Further preferably, based on the total mass of the electrolyte, the content of ethylene carbonate is 10-40wt%, the content of propylene carbonate is 5-13wt%, the content of fluoroethylene carbonate is 5-12wt%, and the content of diethyl carbonate is 35.0-70.0wt%.
[0056] The second aspect of the present invention provides a ternary lithium-ion battery, comprising: a positive electrode sheet, a separator, a negative electrode sheet and the lithium-ion battery electrolyte.
[0057] According to the present invention, preferably, the method for preparing the ternary lithium-ion battery comprises the following steps:
[0058] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrode sheets, and the bare battery cell is obtained by winding; the bare battery cell is placed in an outer package, the lithium ion battery electrolyte is injected into the dried battery, and the battery is allowed to stand, formed, and divided to obtain the ternary lithium ion battery.
[0059] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.
[0060] Example 1
[0061] Preparation of 4,5-difluoro-2-(4,4,4-trifluorobut-2-en-1-yl)-1,3,2-dioxaborane:
[0062] (1 mol) 2-chloro-4-iodo-1,1,1-trifluoro-2-butene (CAS: 191591-41-0) and (1 mol) pinacol borane (CAS: 25015-63-8) are dissolved in a dimethyl sulfoxide solvent, (an appropriate amount of catalyst) Pt(dba)2 is added, and the mixture is heated to 60° C. to react to obtain an intermediate product; (1 mol) of the intermediate product and (1 mol) 1,3-difluoroacetone (CAS: 453-14-5) are dissolved in a tetrahydrofuran solvent, and the mixture is heated to 60° C. and stirred to react to obtain the 4,5-difluoro-2-(4,4,4-trifluorobut-2-en-1-yl)-1,3,2-dioxaborane.
[0063] The present embodiment provides a lithium ion battery electrolyte suitable for a high-temperature and high-nickel system. The electrolyte is configured as follows: in a drying room with a dew point of -50°C, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DMC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 8:2:9:1, and then 1.1 wt% of lithium hexafluorophosphate (LiPF6) based on the mass of the electrolyte, 1 wt% of difluorophosphate (LiPO2F2) based on the total mass of the electrolyte, 1 wt% of vinyl sulfate (DTD), 2 wt% of vinylene carbonate (VC), and 1 wt% of propylene sulfite (PS) are slowly added to the solution, and finally 0.3 wt% of 4,5-difluoro-2-(4,4,4-trifluorobut-2-ene-1-yl)-1,3,2-dioxaborane based on the total weight of the electrolyte is added, and the lithium ion battery electrolyte S1 of Example 1 is obtained after stirring evenly.
[0064] Embodiment 2-4
[0065] The difference between Examples 2-4 and Example 1 is only the different content of the additive A. As shown in Table 1, lithium ion battery electrolytes S2-S4 were obtained.
[0066] Comparative Example 1
[0067] This comparative example provides a lithium ion battery electrolyte suitable for a high-temperature and high-nickel system. The configuration of the electrolyte is as follows: in a drying room with a dew point of -50°C, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DMC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 8:2:9:1, and then 1.1 wt% of lithium hexafluorophosphate (LiPF6) based on the mass of the electrolyte, 1 wt% of difluorophosphate (LiPO2F2) based on the total mass of the electrolyte, 1 wt% of vinyl sulfate (DTD), 2 wt% of vinyl carbonate (VC), and 1 wt% of propylene sulfite (PS) are slowly added to the solution, and the lithium ion battery electrolyte DS1 of comparative example 1 is obtained after uniform stirring.
[0068] Comparative Example 2
[0069] This comparative example provides a lithium-ion battery electrolyte suitable for a high-temperature and high-nickel system. The configuration of the electrolyte is as follows: in a drying room with a dew point of -50°C, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DMC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 8:2:9:1, and then 1.1 wt% of lithium hexafluorophosphate (LiPF6) based on the mass of the electrolyte is slowly added to the solution, and after stirring evenly, the lithium-ion battery electrolyte DS2 of Example 2 is obtained.
[0070] The electrolyte components of Examples 1-4 and Comparative Examples 1-2 are specifically shown in Table 1:
[0071] Table 1
[0072]
[0073]
[0074] Test Case
[0075] The preparation method of the soft pack battery is as follows:
[0076] Preparation of positive electrode: 100 parts of ternary nickel-manganese-cobalt material Li 0.5 Ni 0.2 Co 0.3 MnO2 (NCM523) was mixed with 2 parts of carbon nanotubes, 1 part of conductive agent Super-p, and 2 parts of polyvinylidene fluoride (PVDF) into a uniform paste, which was evenly coated on the positive electrode current collector aluminum foil and vacuum dried at 80°C for 24 hours to obtain a positive electrode sheet.
[0077] Preparation of the negative electrode sheet: 100 parts of graphite material, 1 part of conductive agent Super-p, 1.5 parts of thickener sodium carboxymethyl cellulose (CMC) and 2.5 parts of styrene-butadiene rubber (SBR) were mixed into a uniform paste, evenly coated on the negative electrode collector copper foil, and vacuum dried at 80°C for 24 hours to obtain the negative electrode sheet.
[0078] Preparation of soft-pack batteries: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, place the separator between the positive and negative electrode sheets, and wind them to obtain a bare battery cell; place the bare battery cell in an outer package, inject the above-prepared electrolyte into the dried battery, let it stand, form it, and separate the capacity to complete the preparation of the lithium-ion soft-pack battery.
[0079] Performance Testing:
[0080] (1) Cycle performance: All batteries were placed in a 25°C thermostat, charged to 4.5V at 1C rate, and then constant voltage was set to 0.05C; then discharged to 2.75V at 1C for cycle testing. The percentage obtained by dividing the discharge capacity of each battery at the 500th cycle by the initial discharge capacity of the first cycle was recorded as the capacity retention rate. Ten samples of each type of battery were taken, and the average value was taken. The cycle performance is shown in Table 2.
[0081] (2) Battery expansion rate test: Charge batteries S1-4 and DS1, DS2 at 0.5C with a cut-off voltage of 4.5V, and then charge at a constant voltage of 4.5V with a cut-off current of 0.05C to obtain fully charged batteries. Store the fully charged batteries in a 60°C constant temperature oven for 5 days, 10 batteries for each condition, and take the average value of the results. Use a vernier caliper to measure the thickness of the battery before and after storage, subtract the thickness after storage from the thickness before storage, and divide the thickness difference by the thickness before storage to obtain a percentage that is recorded as the battery expansion rate. The battery expansion rate is shown in Table 2.
[0082] Table 2
[0083] Battery ID Battery expansion rate % Cycle capacity retention rate % S1 30.7 73.2 S2 20.8 90.7 S3 19.6 93.3 S4 34.3 70.1 DS1 57.5 65.6 DS2 76.8 33.4
[0084] As can be seen from Table 2, the batteries S1-S4 prepared in Examples 1-4 of the present application have a low expansion rate while having a good high-voltage capacity retention rate, compared with the batteries DS1 and DS2 prepared in the comparative examples. In addition, the performance of S1 is reduced because the amount of fluorinated borate additive added therein is too low, and the performance of S4 is reduced because the amount of fluorinated borate additive added therein is too high. It can be seen that the additives provided in the present application do not affect the physicochemical properties of the parent electrolyte within a suitable addition range, can significantly reduce the expansion rate of the ternary battery during high-temperature storage at full charge, and improve the safety performance of the ternary battery at high temperature; at the same time, it can stabilize the electrode electrolyte interface, reduce the occurrence of side reactions, and improve the capacity retention rate of the ternary battery during the cycle at a high voltage of 4.5V.
[0085] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A lithium ion battery electrolyte suitable for high voltage working conditions, characterized in that: The lithium ion battery electrolyte comprises: lithium salt, organic solvent and additives; The additive comprises a conventional film-forming electrolyte additive and an additive A, wherein the additive A is selected from at least one of the fluoroborate compounds represented by formula (I). In formula (I), R is C1~C 10 A fluorinated alkyl group, preferably a C1-C3 fluorinated alkyl group, wherein R1, R2, R3, and R4 are each independently selected from H, F, or C1-C 10 Containing a fluorinated alkyl group, and R1, R2, R3, and R4 are not H at the same time; Based on the total mass of the electrolyte, the content of the additive A is 0.01-5.0 wt %, preferably 0.1-3.0 wt %.
2. The lithium ion battery electrolyte according to claim 1, wherein The preparation method of the additive A comprises the following steps: (1) dissolving the fluorinated halogenated olefin represented by formula (II) and pinacol borane in a first organic solvent, heating to 50-60° C., and contacting with a catalyst to react to generate an intermediate product, fluoroallyl boronic acid pinacol ester; the molar ratio of the fluorinated halogenated olefin to the pinacol borane is 1:1; (2) dissolving the intermediate product fluoroallyl boronic acid pinacol ester produced in step (1) and the fluorinated ketone substance represented by formula (III) in a second organic solvent, heating to 50-60° C., and stirring for reaction to produce the additive A; the molar ratio of the intermediate product fluoroallyl boronic acid pinacol ester to the fluorinated ketone substance is 1:1; Formula (II) and formula (III) are as follows: Wherein, in formula (II), R is C1~C 10 A fluorinated alkyl group, preferably a C1-C3 fluorinated alkyl group; in formula (3), R' and R" are each independently selected from C1-C 10 At least one of fluorinated alkyl groups; The first organic solvent is dimethyl sulfoxide solvent; The second organic solvent is tetrahydrofuran; The catalyst is Pd2(dba)3.
3. The lithium ion battery electrolyte according to claim 1, wherein The additive A is selected from at least one of 4,5-difluoro-2-(4,4,4-trifluorobut-2-en-1-yl)-1,3,2-dioxaborane, fluoro-2-(3-fluoroallyl)-1,3,2-dioxaborane, 4,5-difluoro-2-(3-fluoroallyl)-1,3,2-dioxaborane, 4-fluoro-2-(3-fluoroallyl)--5-fluoromethyl-1,3,2-dioxaborane and 2-(3-fluoroallyl)-4,5-bisfluoromethyl-1,3,2-dioxaborane.
4. The lithium ion battery electrolyte according to claim 1, wherein The conventional film-forming electrolyte additive is selected from at least one of difluorophosphate, vinyl sulfate, vinylene carbonate and propylene sulfite; Based on the total mass of the electrolyte, the content of the conventional film-forming electrolyte additive is 3.0-5.0wt%.
5. The lithium ion battery electrolyte according to claim 1, wherein The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium perchlorate and lithium hexafluoroarsenate, preferably selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide; Based on the total mass of the electrolyte, the content of the lithium salt is 0.5-3wt%.
6. The lithium ion battery electrolyte according to claim 1, wherein The organic solvent is a carbonate compound; preferably, the carbonate compound includes cyclic carbonate and chain carbonate; wherein the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate and fluoroethylene carbonate; and the chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
7. The lithium ion battery electrolyte according to claim 6, wherein: The organic solvent is a mixture of ethylene carbonate, propylene carbonate, fluoroethylene carbonate and diethyl carbonate.
8. The lithium ion battery electrolyte according to claim 7, wherein Based on the total mass of the electrolyte, the content of ethylene carbonate is 10-40wt%, the content of propylene carbonate is 5-13wt%, the content of fluoroethylene carbonate is 5-12wt%, and the content of diethyl carbonate is 35.0-70.0wt%.
9. A ternary lithium-ion battery, characterized in that: include: A positive electrode sheet, a separator, a negative electrode sheet and a lithium ion battery electrolyte as claimed in any one of claims 1 to 8.
10. The ternary lithium-ion battery according to claim 9, wherein: The preparation method of the ternary lithium-ion battery comprises the following steps: The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an outer package, the lithium ion battery electrolyte described in any one of claims 1 to 8 is injected into the dried battery, and the battery is allowed to stand, formed, and divided to obtain the ternary lithium ion battery.
Citation Information
Patent Citations
Incombustible high voltage electrolyte and preparation method and application thereof
CN109830752A